The Creative Process in Small and Medium-Sized Enterprises (GESTIÓN Y TENDENCIAS, 2019)
Chile is undergoing profound social change. A range of actors are reflecting on the future. As regards companies, we have long instilled the idea that their ultimate purpose is to maximize shareholder profits, but under this view other elements of society may be harmed or neglected. This moment is therefore an opportunity to transform and renew the way things are done in companies as well, particularly the most vulnerable ones such as small and medium-sized enterprises (SMEs).